2000
DOI: 10.1093/nar/28.21.4097
|View full text |Cite
|
Sign up to set email alerts
|

Purification and cloning of cytotoxic ribonucleases from Rana catesbeiana (bullfrog)

Abstract: Ribonucleases with antitumor activity are mainly found in the oocytes and embryos of frogs, but the role of these ribonucleases in frog development is not clear. Moreover, most frog ribonuclease genes have not been cloned and characterized. In the present study, a group of ribonucleases were isolated from Rana catesbeiana (bullfrog). These ribonucleases in mature oocytes, namely RC-RNase, RC-RNase 2, RC-RNase 3, RC-RNase 4, RC-RNase 5 and RC-RNase 6, as well as liver-specific ribonuclease RC-RNase L1, were pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 31 publications
1
63
0
Order By: Relevance
“…The novel sequences are those of the 200 series: rc-203, rc-204, rc-208, rc-212, and rc-218. Several of these sequences were also identified by PCR amplification but not reported in the studies performed by Liao et al (2000). The amino terminal "Q" of these novel sequences has been inferred based on similarity to the amino acid sequence of rc-RNase (rc-RN), whose terminus was determined directly via protein sequencing (Titani et al 1987); the 22 amino acid signal sequences encoded by the full length cDNAs are not shown.…”
Section: Identification Of Novel Ribonucleasementioning
confidence: 99%
See 1 more Smart Citation
“…The novel sequences are those of the 200 series: rc-203, rc-204, rc-208, rc-212, and rc-218. Several of these sequences were also identified by PCR amplification but not reported in the studies performed by Liao et al (2000). The amino terminal "Q" of these novel sequences has been inferred based on similarity to the amino acid sequence of rc-RNase (rc-RN), whose terminus was determined directly via protein sequencing (Titani et al 1987); the 22 amino acid signal sequences encoded by the full length cDNAs are not shown.…”
Section: Identification Of Novel Ribonucleasementioning
confidence: 99%
“…Liao et al (Huang et al 1998) were the first to isolate a cDNA encoding a Rana ribonuclease (rc-RNase), and found mRNA expression in the liver rather than in oocytes where the protein is ultimately localized. Most recently, Liao et al (2000) reported five novel cDNA sequences encoding R. catesbeiana ribonucleases (rc-01 encoding rc-L1, and rc-02, rc-03, rc-04, and rc-06) found in oocyte yolk granule extracts and liver and Chen et al (2000) described a gender-specific cytotoxic ribonuclease (rp-rap) from R. pipiens.…”
Section: Introductionmentioning
confidence: 99%
“…Several RNase A ribonucleases of the frog genus Rana have been isolated (15)(16)(17)(18), including the cancer biotherapeutic agent, onconase (19). Also characterized are several RNase A ribonucleases from birds (14, 20 -22) and reptiles (23)(24)(25).…”
mentioning
confidence: 99%
“…(10,11,16,17). Notably, it has been revealed that RC-RNase is not cytotoxic to normal cells (10,15). However, the ability of RC-RNase to inhibit glioblastoma cell growth is not clear.…”
Section: Statistical Analysis Student's T-testmentioning
confidence: 99%
“…RC-RNase and Onconase have been revealed to demonstrate antitumor activity (10)(11)(12)(13). Previous studies have reported that RC-RNase is able to exert cytotoxic effects in various tumor cells, including cervical cancer, leukemia, hepatoma and breast cancer cells (11,(14)(15)(16). In addition, numerous studies have indicated that RC-RNase is able to trigger distinct cell death mechanisms in various tumor cell types (10,11,14,17).…”
Section: Introductionmentioning
confidence: 99%